2D Hexagonal Assemblies of Amphiphilic Double‐Helical Poly(phenylacetylene) Homopolymers with Enhanced Circularly Polarized Luminescence and Chiral Self‐Sorting. Issue 52 (23rd November 2022) - Cai, Siliang; Huang, Yihan; Xie, Siyu; Wang, Sheng; Guan, Yan; Wan, Xinhua; Zhang, Jie
Abstract: Two‐dimensional (2D) chiral materials have been attracting immense attentions owing to their unique properties. Herein, we successfully developed a unique assembly strategy of amphiphilic homopolymers to construct stable free‐standing 2D chiral nanosheets in solution. The amphiphilic poly(phenylacetylene) (PPA) homopolymers bearing the hydrophobic and hydrophilic dendritic side chains adopt a DNA‐like double‐helical conformation. The regular hexagonal nanosheets were formed in THF/EtOH through nucleation and epitaxial growth. The sizes of the nanosheets can be modulated from nanometers to submillimeters upon varying the ratio of binary solvents, while the thickness is linearly correlated with the molecular weights. The 2D architecture can significantly enhance the CPL of polymers with a high dissymmetry factor ≈0.1. Driven by a discrimination of helical conformation, the PPAs can self‐sort into homochiral 2D nanosheets, as directly visualized by using fluorescent microscopy. Abstract : A unique assembly strategy has been developed to generate free‐standing two‐dimensional chiral nanomaterials based on amphiphilic poly(phenylacetylene) homopolymers, which bear hydrophobic and hydrophilic dendritic side chains and adopt a DNA‐like double‐helical conformation. The aggregates form modulable 2D hexagonal nanosheets directly in solution, with enhanced CPL and chiral self‐sorting behavior.